2022
DOI: 10.1111/wej.12825
|View full text |Cite
|
Sign up to set email alerts
|

2,4‐dinitroanisole transformation during advanced oxidation with ultraviolet light emitting diodes and hydrogen peroxide

Abstract: This study investigated the kinetics and reaction mechanisms associated with advanced oxidation of 2,4-dinitroanisole (DNAN) with light emitting diodes (LEDs) in the UV/H 2 O 2 process. The pseudo first-order reaction rate constants for DNAN oxidation depended on the H 2 O 2 /DNAN molar ratio and were between 0.017 and 0.026 min À1 .Hydroxyl radical scavenging was strongly implicated by the experimental results. High mass spectrophotometric chromatograms showed the presence of several by-products, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Their experiments were done over a narrower range of molar peroxide ratios and with higher initial BPA concentrations (0.22 vs. 0.044 mM). The pseudo first‐order rate constants for DNAN removal were similar to those reported by Burdsall et al (2023) and Su et al (2019), who implemented UV/H 2 O 2 to remove DNAN from wastewater in beakers equipped with 13 W mercury lamps. Therefore, the current and previous studies form a clear consensus regarding the removal kinetics of BPA and DNAN.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Their experiments were done over a narrower range of molar peroxide ratios and with higher initial BPA concentrations (0.22 vs. 0.044 mM). The pseudo first‐order rate constants for DNAN removal were similar to those reported by Burdsall et al (2023) and Su et al (2019), who implemented UV/H 2 O 2 to remove DNAN from wastewater in beakers equipped with 13 W mercury lamps. Therefore, the current and previous studies form a clear consensus regarding the removal kinetics of BPA and DNAN.…”
Section: Resultssupporting
confidence: 82%
“…Radical abstraction of the methoxy group followed by the addition of •OH to DNAN forms 2,4 DNP and •OCH 3 radicals (Figure 4). Abstraction of o-NO 2 , followed by combining the DNAN radical fragment with •OH, forms 2-hydroxy-4 nitroanisole along with a •NO 2 radical (Burdsall et al, 2023). Abstraction of the p-NO 2 from DNAN, followed by combining with an •OH, forms 2-nitro-4-hydroxyanisole alongside a •NO 2 radical (Burdsall et al, 2023).…”
Section: Transformation Pathways and Reaction Mechanisms For Dnanmentioning
confidence: 99%
See 2 more Smart Citations
“…Various emerging treatment strategies have been investigated for IHEs. For example, electrochemical reduction, chemical reduction using bimetallic and zerovalent iron particles, biological degradation, photochemical degradation, , alkaline hydrolysis, and advanced oxidation processes (AOPs) , have been applied to treat aqueous DNAN solutions. While these studies demonstrated DNAN destruction to varying extents, several of the treatment strategies have serious drawbacks.…”
Section: Introductionmentioning
confidence: 99%